The collagen diet : a 28-day plan for sustained weight loss, glowing skin, great gut health, and a younger you - Axe, Josh (Little, Brown Spark, 2019)
Today, interest in dietary collagen is growing at an astounding rate, and with good reason. The benefits of a collagen-rich diet are remarkable, ranging from better weight control to enhanced digestion, clearer skin, reduced inflammation, and improved immune function. Dietary collagen provides a unique blend of amino acids and other compounds, making it critical for everyone, including infants, young children, the elderly, athletes, pregnant women, new mothers, and adult men and women. Simply put: When we don't get enough of the beneficial compounds found in collagen-rich foods, we experience more injuries, chronic aches and pain, digestive issues, and other symptoms associated with aging. And most people don't get enough. Collagen is the missing ingredient that can help all of us live longer, healthier, more vital lives. In The Collagen Diet, Dr. Axe describes how collagen helps maintain the structure and integrity of almost every part of the body. You'll learn how your skin, hair, nails, bones, disks, joints, ligaments, tendons, arterial walls, and gastrointestinal tract all depend on the consumption of collagen-rich foods. Featuring a twenty-eight-day meal plan, seventy mouthwatering recipes, and specific advice for supporting your body's collagen production with exercise and lifestyle interventions, The Collagen Diet provides everything you need to take advantage of this overlooked cornerstone of modern health.